Development and Characterization of Spray-Dried Curcumin-Lecithin Complexes with Improved Solubility and In Vitro Digestive and Thermal Stability - Mankan, Erkan; Sagdic, Osman; Karadag, Ayse (MDPI, 2025)
Curcumin, a bioactive polyphenol from turmeric, faces significant challenges in food and pharmaceutical applications due to its poor water solubility, low stability, and limited bioavailability. In this study, curcumin-lecithin complexes (phytosomes) were spray-dried using maltodextrin as the carrier polymer to produce free-flowing powders with improved physicochemical properties. The powders were characterized based on moisture content, particle size, morphology, curcumin loading, thermal behavior, and stability under simulated gastrointestinal and thermal conditions. The lecithin-curcumin complexes exhibited high entrapment efficiency (up to 94%), a predominantly amorphous structure, and improved thermal and digestive stability compared to free curcumin. Particle size and wettability were influenced by carrier and curcumin ratios, with maltodextrin enhancing powder flowability and apparent solubility. Morphological analyses revealed spherical particles with core-shell structures, confirming successful complexation. The complexes protected curcumin from degradation at intestinal pH and elevated temperatures, highlighting their potential for enhanced bioavailability. These findings demonstrate that spray-dried curcumin-lecithin complexes with maltodextrin carriers offer a promising strategy to overcome curcumin's solubility and stability limitations, supporting their application in functional foods and pharmaceuticals.
Keywords: phytosome; maltodextrin; TEM; SEM; simulated digestion; PHOSPHOLIPID COMPLEX; ORAL BIOAVAILABILITY; DAIRY POWDERS; DELIVERY; PERMEABILITY; SYSTEM; Food Science & Technology